Max Weber in the United States - Scaff, Lawrence A. (SocietàMutamentoPolitica, 2014)
In his contribution L. Scaff outlines the reception history of Max Weber’s work from its beginnings down to the present. It highlights the importance of the first translations, including those by prominent American authors and particularly those who had studied in Germany; and then in the post-war years the role of emigrants familiar with Weber’s work. The establishment of Weber texts as compulsory reading in the curricula of American colleges also played a significant role. The striking readiness, even ease, with which Weber was received in America is something Scaff deduces from three “narratives that captured the imagination of the American audience”. The first is the narrative of voluntarism, i.e. “the way in which Weber developed his conception of the sect and its effects on the individual and society”. Next is the narrative of achievement, in the sense of “mastery of the world”, preceded by “mastery of the self”, which “when put into practice entailed the conquest of the New World’s primordial wilderness”. Finally there is the narrative of redemption as “the most potent founding myth of the American experience”: “The quest for salvation that began as a religiously inspired message became transformed into a secularized cultural theme: the search for the possibility of breaking free from constraints in order to create a better life, to renew the self, to gain a second chance by atoning for moral failures, and to find reconciliation with God, humankind, and the world.”